2014
DOI: 10.1007/s12032-014-0118-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of three regulation enzymes in glycolysis in esophageal squamous cell carcinoma: association with survival

Abstract: Enhanced glycolysis is a common trait of many types of human cancers. This study was to detect the expression pattern of three regulatory enzymes during glycolysis in esophageal squamous cell carcinoma (ESCC) and to investigate their correlation with patients' outcome based on banked pathology material. A total of 141 surgically resected specimens of primary ESCC patients without prior treatments were retrospectively recruited from the First Affiliated Hospital of Wenzhou Medical College Hospital from 2007 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Four original studies consistently elucidated the prognostic value of PKM2 expression for poor clinical outcome [ 17 , 24 , 95 , 96 ], with the prognostic significance confirmed by multivariate analysis in 3 original studies [ 17 , 95 , 96 ]. These findings provide evidence of the significance of PKM2 expression as a prognostic biomarker in ESCC.…”
Section: Resultsmentioning
confidence: 99%
“…Four original studies consistently elucidated the prognostic value of PKM2 expression for poor clinical outcome [ 17 , 24 , 95 , 96 ], with the prognostic significance confirmed by multivariate analysis in 3 original studies [ 17 , 95 , 96 ]. These findings provide evidence of the significance of PKM2 expression as a prognostic biomarker in ESCC.…”
Section: Resultsmentioning
confidence: 99%
“…The band with 60 kDa MW was BSA, and the other bands were swine TG, enolase, pyruvate kinase and phosphoglyceraldehyde dehydrogenase. Among these five proteins, BSA served as a positive control protein that was artificially supplemented, swine TG was previously shown to be present in the follicular lumen, and the other three proteins were key glycolysis-associated enzymes, which have previously been identified to be critical in anaerobic glycolysis of glucose (1315). …”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, PKM2 has emerged as a major player in cancer development because it provides a metabolic advantage to cancer cells to utilize phosphor-metabolites upstream of pyruvate as precursors for the synthesis of lipids, amino acids and nucleic acids [19]. Several studies to date have found that increased mRNA expression or protein expression of glycolytic enzymes correlates with esophageal carcinoma cell progression [16]. The deregulation of several glycolytic genes, including GLUT4, HK2, PFKBP3, and PKM2, was determined to be responsible for the reprogramming of glucose metabolism in NPC cells.…”
Section: Discussionmentioning
confidence: 99%